The Implementation and Challenges of ASN Career Development Based on Merit System in Badung Regency Government - Sukma Kartana; Oka Suryadinatha Gorda (Green Publisher Indonesia, 2025)
This research was conducted to find out how the career development of state civil servants (ASN) is regulated based on the merit system according to Law Number 5 of 2014 concerning the State Civil Apparatus (ASN), where in the merit system the highest priority is qualifications that include in the selection and recruitment of employees, competencies, and placement of ASN itself. The merit system refers to assessing and recognizing a person's abilities, competencies, performance, and work achievements. In this system, ASN's promotion and career development are based on the quality of an individual's objective performance, not subjective factors such as nepotism. Using quantitative research methods, it was concluded that, first, the development of employee careers even though they had developed a merit system, it turned out that the most dominant thing was coaching from the leadership, the leadership seemed to have the prerogative to determine whether an employee could quickly achieve his career or experience obstacles Second, the main factor that affects career development in the implementation of the merit system turns out to lie in the political factor in the organization, where the role of politics is so significant in determining who sits where in career development, and the third challenge faced in the career development of ASN in Badung Regency lies in the mindset of employees, some employees still assume that career development is not very important, so they don't want to get too involved to understand all kinds of government policies related to employees' careers.